FINANCIAL PERFORMANCE ANALYSIS OF OLD AND NEW GENERATION BANKS – A COMPARATIVE STUDY - Mary, J. Nisha; Priyadharisini, Dr. Mary J. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Banks play an important and diverse role in the development of the economy. Banks are utilizing the capital deficit in the country for production. Currently, the Indian banking sector is going through significant changes due to global developments such as increasing competition, increasing consumer preferences, decreasing interest margins, increasing impact and weakening prices. Profitability, competitiveness and financial stability are important targets to be pursued. The main objective of this study is to compare the assets of old and new banks in India for the next five years from 2016 to 2020. In this research paper, researchers used the tabular model for analysis. For this test, we selected regional banks, old companies and new generation banks. The results show that new generation banks perform better than old ones.